Arte infantil y educación artística - RICARDO Marín; MARÍA JOSÉ Bustamante; LOURDES Casares; NICOLÁS Flores; TERESA García; MANUEL Puentes; MARÍA Ruiz; Virtudes Martínez (Arte, Individuo y Sociedad, 2002)
Sin resumen